Seal, replacement or monitoring amalgam restorations with occlusal marginal defects? Results of a 10-year clinical trial - Moncada, Gustavo; Fernández, Eduardo; Mena, K.; Martin, Javier; Vildósola, Patricio; Oliveira Júnior, Osmir Batista de [UNESP]; Estay, Juan; Mjör, Ivar A.; Gordan, Valeria V. (Elsevier B. V., 2015)
The aim of this prospective and blind clinical trial was to assess the effectiveness of sealing localized marginal defects of amalgam restoration that were initially scheduled to be replaced. A cohort of twenty six patients with 60 amalgam restorations (n=44Class I and n=16Class II), that presented marginal defects deviating from ideal (Bravo) according to USPHS criteria, were assigned to either sealing or replacement groups: A: sealing n=20, Replacement n=20, and no treatment (n=20). Two blind examiners evaluated the restorations at baseline (K=0.74) and after ten years (K=0.84) according with USPHS criteria, in four parameters: marginal adaptation (MA), secondary caries (SC), marginal staining (MS) and teeth sensitivity (TS). Multiple comparison of restorations degradation/upgrade was analyzed by Friedman test and the comparisons within groups were performed by Wilcoxon test. After 10 years, 44 restorations were assessed (73.3%), Group A: n=14 and Group B: n=16; and Group C: n=14 sealing and replacement amalgam restorations presented similar level of quality in MA (p=0.76), SC (p=0.25) and TS (p=0.52), while in MS (p=0.007) presented better performance in replacement group after 10-years. Most of the occlusal amalgam restorations with marginal gaps showed similar long term outcomes than the restorations were sealed, replaced, or not treated over a 10-year period. Most of the restorations of the three groups were clinically acceptable, under the studied parameters. All restorations had the tendency to present downgrade/deterioration over time.
Keywords: Amalgam; Clinical trail; Marginal gaps; Replacement